2016
DOI: 10.1016/j.heares.2016.03.009
|View full text |Cite
|
Sign up to set email alerts
|

The calyx of Held in the auditory system: Structure, function, and development

Abstract: The calyx of Held synapse plays an important role in the auditory system, relaying information about sound localization via fast and precise synaptic transmission, which is achieved by its specialized structure and giant size. During development, the calyx of Held undergoes anatomical, morphological, and physiological changes necessary for performing its functions. The large dimensions of the calyx of Held nerve terminal are well suited for direct electrophysiological recording of many presynaptic events that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 152 publications
(287 reference statements)
0
28
0
Order By: Relevance
“…During maturation, the calyx transforms into a high-fidelity synapse that can sustain action 533 potential (AP) firing upwards to a kilohertz (Baydyuk et al, 2016). Since AP firing is an 534 energetically expensive process (Harris et al, 2012), this suggested that mitochondria levels are 535 increased in the axon also.…”
Section: Mito-apex2 Expression Does Not Alter Synaptic Transmission 445mentioning
confidence: 99%
See 1 more Smart Citation
“…During maturation, the calyx transforms into a high-fidelity synapse that can sustain action 533 potential (AP) firing upwards to a kilohertz (Baydyuk et al, 2016). Since AP firing is an 534 energetically expensive process (Harris et al, 2012), this suggested that mitochondria levels are 535 increased in the axon also.…”
Section: Mito-apex2 Expression Does Not Alter Synaptic Transmission 445mentioning
confidence: 99%
“…The calyx of Held, a large glutamatergic presynaptic terminal in the medial nucleus of the 87 trapezoid body (MNTB) in the auditory brainstem undergoes considerable morphological and 88 physiological transformations around the onset of hearing at the end of the second postnatal week 89 (Baydyuk et al, 2016). At the physiological level, the calyx of Held/MNTB synapse shifts from 90 exhibiting frequent synaptic failures before hearing onset to reliable synaptic transmission at firing 91 rates up to several hundred Hertz (Taschenberger and von Gersdorff, 2000).…”
Section: Introduction 77mentioning
confidence: 99%
“…In the present study, we evaluated the effect of virally expressed GCaMP6m on synaptic transmission properties in the presynaptic terminal at an identified central synapse, the calyx of Held. The calyx of Held synapse is one of the best‐characterized central synapses, and its synaptic properties such as vesicle recycling, short‐term depression, and Ca 2+ buffering mechanisms have been carefully defined (Baydyuk, Xu, & Wu, ; Nakamura & Takahashi, ; Nakamura, Reva, & DiGregorio, ; Taschenberger, LeĂŁo, Rowland, Spirou, & von Gersdorff, ; Taschenberger, Woehler, & Neher, ; von Gersdorff & Borst, ) Thus, this synapse provides an excellent model for presynaptic‐specific genetic manipulations and their effects on synaptic transmission. Our results show that presynaptic GCaMP has a profound effect on synaptic transmission by reducing SV release probability, including responses evoked at low frequency, where intracellular Ca 2+ is highly spatially localized.…”
Section: Introductionmentioning
confidence: 99%
“…Although multiple roles for STP have been suggested [18], there is little direct experimental evidence to support a particular function. Similarly, the calyx of the Held synapse in the mammalian auditory system, due to its accessibility and interesting dynamics [19], has been studied extensively for mechanisms of STP. However, no clear functional role for STP at this synapse has been found [20,21].…”
Section: Introductionmentioning
confidence: 99%